Geochemical and isotope evidence for groundwater mineralization in a semi-arid river basin, Sri Lanka. (January 2021) - Senarathne, Sachintha; Jayawardana, J.M.C.K.; Edirisinghe, E.A.N.V.; Chandrajith, Rohana
Abstract: Mineralization of groundwater has become a major concern in the coastal, arid, and semi-arid regions throughout the world. The lower segment of the Walawe river stretches through a semi-arid region in Southern Sri Lanka, and groundwater has become an important source of freshwater for the region. A hydrogeochemical study was carried out to identify the sources and processes of groundwater mineralization in the lower region of the Walawe river basin. The groundwater composition was analysed using samples collected from 32 locations during the pre- and post-monsoon periods. The analysis of groundwater revealed that the groundwater composition of the region was dominated by HCO3 −, Cl −, and SO4 2-, which were mostly balanced by Na +, Ca 2+, and Mg 2+ . Ionic relationships of major solutes indicated that anthropogenic influences such as effects of fertilizer applications during the post-monsoon period and notable effects of evaporation during both periods. δ 18 O and δ 2 H signatures of the groundwater in the region showed deviations from the regional meteoric water line suggesting intensive evaporation events (δ 2 H = 5.6 *δ 18 O – 1.37, r = 0.98). Particularly, isotope values of pre-monsoon samples in the study region indicated contributions of north-east monsoon and first inter-monsoon. Solute geochemistry and stable isotope evidences from the region indicate that groundwater salinity in the area is mainly caused by anthropogenic inputs of solutes through agricultural activities and modified heavily by intensive evaporation. Principle Component Analysis indicated higher heavy metal concentrations in the groundwater during the post-monsoon period in comparison to that of the pre-monsoon period possibly originated from anthropogenic activities. The finding of this study suggested the need for comprehensive groundwater management plans and monitoring programs for ensuring sustainable management of groundwater in the lower Walawe river basin. Graphical abstract: Image 1 Highlights: Groundwater mineralization in semi-arid review basin in Sri Lanka was investigated. Geochemical and isotope fingerprinting of groundwater were identified. Evidences showed an increasing salinity in groundwater in certain parts of the basin. Groundwater in the terrain is highly vulnerable for the predicted climate change.